PENGARUH KUALITAS PELAYANAN, CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN SEPEDA MOTOR HONDA BEAT DI PT. NUSANTARA SAKTI SEMARANG - Irna Windu Prasetyani; Handoyo Djoko Waluyo; Agung Budiatmo (Jurnal Ilmu Administrasi Bisnis, 2014)
This research purpose to find out the influence of service quality, brand image and product quality onpurchase decision of Honda BeAT motorcycle’s consumer at PT. Nusantara Sakti Semarang. This researchincluded in explanatory. Taked 100 respondents as sample with purposive sampling method. Collecting dataused questionnaire. The datas analized by validity and reliability, cross table, a simple regression analysis,regression analysis, and hypothesis testing using the formula t and F count. The result of this research showthat service quality have significant influence on purchase decision, brand image have significant influence onpurchase decision, product quality have significant influence on purchase decision, and service quality, brandimage and product quality in partial and simultaneous have significant influence on purchase decision.